Learning America : one woman's fight for educational justice for refugee children - Mufleh, Luma (Mariner Books, 2021)
"It was a wrong turn that changed everything. When Luma Mufleh--a Muslim, gay, refugee woman from hyper-conservative Jordan--stumbled upon a pick-up game of soccer in Clarkston, Georgia, something compelled her to join. The players, 11- and 12-year-olds from Liberia, Afghanistan, and Sudan, soon welcomed her as coach of their ragtag but fiercely competitive group. Drawn into their lives, Mufleh learned that few of her players, all local public school students, could read a single word. She asks, "Where was the America that took me in? That protected me? How can I get these kids to that America?" Learning America traces the story of how Mufleh grew a group of kids into a soccer team and then into a nationally acclaimed network of schools for refugee children. The journey is inspiring and hard-won: Fugees schools accept only those most in need; no student passes a grade without earning it; the failure of any student is the responsibility of all. Soccer as a part of every school day is a powerful catalyst to heal trauma, create belonging, and accelerate learning. Finally, this gifted storyteller delivers provocative, indelible portraits of student after student making leaps in learning that aren't supposed to be possible for children born into trauma--stories that shine powerful light on the path to educational justice for all of America's most left-behind." -- Publisher's website.